Microsolvation of morpholine, a bidentate base: the importance of cooperativity - Vallejos, Margarita (2012)
The structure, relative energies and bonding in morpholine(water)n (n = 1-4) clusters have beeninvestigated at the B3LYP/6-311+G(3df,2p)//B3LYP/6-311+G(d,p) level of theory. Cooperative effects have been analyzed through the use of structural, energetic and electron density indexes. Our analysis shows that these effects are crucial to trace the relative stability of the complexes formed. In all cases water molecules prefer to self-associate forming chains in which each individual molecule behaves as a HB donor and HB acceptor. The chain so formed behaves in turn as HB donor and HB acceptor with respect to morpholine, being the most stable arrangements those in which the NH group of morpholine behaves simultaneously as HB donor and HB acceptor. Higher in energy lie complexes in which the HB acceptor continues to be the NH group, but the HB donor is a CH group, or alternative structures in which the HB acceptor is the ether-like oxygen of morpholine and the HB donor its NH group.  Cooperativity increases with the number of solvent molecules, but there is a clear attenuation effect. Thus, whereas the additive interaction energy on going from dihydrated to trihydrated species increases by a factor of 3, this increase is about half on going from trihydrated to tetrahydrated complexes.